PENGARUH KOMPETENSI PENYALUR (PT.TEMPO SCAN PASIFIC LUBUKLINGGAU) DAN KUALITAS LAYANAN TERHADAP KEPUASAN (BIDAN) DI LUBUKLINGGAU, MUSIRAWAS, DAN MUSI RAWAS UTARA - Purna Irawan (Jurnal Media Ekonomi (JURMEK), 2020)
The purpose is to knowed competency, service to satisfaction. The sample are 96 People. The collection data used quisioner, observation, and document. Partial test (t-test) doing to know influence independent variable and dependent variable as Simultan. The recapitulation regression linier, it’s ttest is 4,921 > ttabel = 0,67705 And the significat sig t is 0,000. Its means simultan is independent variable (product quality and service) have influence to dependent variable (the statisfaction). Simultan test (F test) are Ftest is 57,099 > Ftabel = 3,94 and the signification sig F is 0,000. So its partial signifation in the independent variable (quality product and service) have influence to dependent variable (statisfaction). R square is have a positif colleration is 0,817. Its mean the colleration Independent variable and dependent variable with simultan is hight as 8,17%. Than the colleration is good if the value as I with asumsy the onether dependent is cosntan.